About the product of inner radii of pairwise non-overlapping domains - Bakhtina, G.P.; Dvorak, I. Y.; Denega, I. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
A general problem of the description of extremal configurations maximizing the product of the inner radii of mutually non-overlapping domains is studied.